SOLPS analysis of the MAST-U divertor with the effect of heating power and pumping on the access to detachment in the Super-x configuration. (26th August 2015) - Havlíčková, E; Harrison, J; Lipschultz, B; Fishpool, G; Kirk, A; Thornton, A; Wischmeier, M; Elmore, S; Allan, S
Abstract: SOLPS simulations of MAST-U have been carried out to identify in more detail the physics and operational properties of novel divertor configurations such as Super-x divertor (SXD), in particular the physics of detachment. A well diagnosed L-mode discharge from MAST has been utilised to determine L-mode transport coefficients representative for MAST-U L-mode plasmas. Simulations show that under the same core plasma conditions, the MAST-U SXD is strongly detached whilst the conventional divertor (CD) is not (1 eV versus 20 eV at the divertor plate). The detachment and higher power losses (1.6×) in the SXD versus the attached CD lead to a factor of 25 reduction in the target power load and are attributed to changes in radial location of the target. An attached regime can be established for the SXD in L-mode for higher pumping speed and/or heating power. In contrast, the simulation predicts that the MAST-U CD requires 3× higher density or 4× reduced power than the SXD to detach. Comparing two versions of the SXD, each with a different amount of poloidal expansion in the region near the divertor plate, we find that the effect of additional poloidal flux expansion of the SXD on an already detached plasma is small for a change in flux expansion in volume by a factor of 2–3 (target temperature 0.7 eV versus 1.1 eV). The poloidal flux expansion re-arranges the radiation pattern with only a small increase in divertor power losses (1.06×) compared to changing from the CD to SXD topology. By artifically increasing the leakage from the divertor chamber, we confirmed that the tight closure of the divertor region leads to strong increases in neutral density with concomitant power losses.